Towards the rational design of ylide-substituted phosphines for gold(i)-catalysis: from inactive to ppm-level catalysis. Issue 12 (10th February 2021) - Handelmann, Jens; Babu, Chatla Naga; Steinert, Henning; Schwarz, Christopher; Scherpf, Thorsten; Kroll, Alexander; Gessner, Viktoria H.
Abstract : Modification of the backbone in ylide-substituted phosphines allowed a remarkable boost in the catalytic activity, thus enabling a series of gold catalyzed transformations at very low catalyst loadings. Abstract : The implementation of gold catalysis into large-scale processes suffers from the fact that most reactions still require high catalyst loadings to achieve efficient catalysis thus making upscaling impractical. Here, we report systematic studies on the impact of the substituent in the backbone of ylide-substituted phosphines (YPhos) on the catalytic activity in the hydroamination of alkynes, which allowed us to increase the catalyst performance by orders of magnitude. While electronic changes of the ligand properties by introduction of aryl groups with electron-withdrawing or electron-donating groups had surprisingly little impact on the activity of the gold complexes, the use of bulky aryl groups with ortho -substituents led to a remarkable boost in the catalyst activity. However, this catalyst improvement is not a result of an increased steric demand of the ligand towards the metal center, but due to steric protection of the reactive ylidic carbon centre in the ligand backbone. The gold complex of the thus designed mesityl-substituted YPhos ligand YMes PCy2, which is readily accessible in one step from a simple phosphonium salt, exhibited a high catalyst stability and allowed for turnover numbers up to 20 000 in the hydroamination of a series of different alkynes and amines. Furthermore, the catalyst was also active in more challenging reactions including enyne cyclisation and the formation of 1, 2-dihydroquinolines.